Struktur Sel Daun Sirih Bermanfaat Sebagai Antidislipidemia dan Antioksidan untuk Mencegah Penyakit Jantung - Lisa Fitriana; Ardi Mustakim (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Decoction water betel leaf is a traditional Balinese medicine containing the active compound hydroxychavikol, has antioxidant and antidyslipemic activity. From the results of the study it was reported that decoction water of betel leaf contains the active compound hydroxycavicol (HC). The active compound hiroksikavikol has activity as an antioxidant and antidyslipidemia. As an anti-oxidant, it can scavenge ROS and inhibit the activity of free radicals. As an antidyslipidemia, it can normalize lipid metabolism by lowering total cholesterol, triglyceride, LDL and VLDL levels and increasing blood serum HDL levels. Oxidative stress and dyslipidemia are major risk factors for heart disease caused by atherosclerosis. Atherosclerosis is the occurrence of plaque formation in the lumen of blood vessels triggered by oxidative stress through endothelial cell dysfunction, inflammation and lipid peroxidation. Oxidative stress causes endothelial cell dysfunction, increased contractility, VSMC growth, monocyte invasion and lipid peroxidation, inflammation and increased deposition of extracellular protein matrix. Based on these things, it was concluded that HC loloh boiled water of betel leaf has antioxidant and antidyslipidemic activity to prevent heart disease.